Tracing Nitrogen Metabolism in Mouse Tissues with Gas Chromatography-Mass Spectrometry - Xu, Rong (Bio Protoc, 2021)
Nitrogen-containing metabolites including ammonia, amino acids, and nucleotides, are essential for cell metabolism, growth, and neural transmission. Nitrogen metabolism is tightly coordinated with carbon metabolism in the breakdown and biosynthesis of amino acids and nucleotides. Both nuclear magnetic resonance spectroscopy and mass spectrometry including gas chromatography-mass spectrometry (GC MS) and liquid chromatography (LC MS) have been used to measure nitrogen metabolism. Here we describe a protocol to trace nitrogen metabolism in multiple mouse tissues using (15)N-ammonia coupled with GC MS. This protocol includes detailed procedures in tracer injection, tissue preparation, metabolite extraction, GC MS analysis and natural abundance corrections. This protocol will provide a useful tool to study tissue-specific nitrogen in metabolically active tissues such as the retina, brain, liver, and tumor.